Peran Edukasi Hukum dalam Mengurangi Angka Pernikahan Dini di SMA IT Harapan Bunda Kelurahan Pedurungan Lor Kota Semarang - Bagas Budi Santoso; Saad Syamsul Arifin (Jurnal Pengabdian KOLABORATIF, 2025)
Early marriage in Indonesia is still a significant social problem, despite efforts to reduce it. Data from the Central Statistics Agency (BPS) shows that the rate of early marriage in this country is still relatively high, namely around 6% to 10% of total marriages involving couples under the age of 18. Early marriage often has a negative impact on children's health and education, as well as resulting in social and economic inequality. Efforts by the government and various non-government organizations to increase legal awareness and education regarding the risks of early marriage continue, including legal education for SMA IT Harapan Bunda students held by the KKN post 44 groups in Pedurungan Lor Village. The method used is lecture and question and answer by conveying legal information directly and interactively. In this method, lectures function as a means to convey basic knowledge regarding legal regulations related to marriage as well as the legal impacts of early marriage. The question and answer session then provided the opportunity for participants to ask questions and discuss directly with the resource person. This approach not only increases participants' understanding of the legal consequences of early marriage but also makes it possible to overcome doubts and get direct answers to the specific issues they face. The results of this activity show that students gain a deeper understanding of the legal regulations related to marriage and the long-term impacts of early marriage. This increase in knowledge, as reflected in the results of discussions and Q&A, shows that students are becoming more aware of the importance of delaying marriage until they reach adulthood and are emotionally and financially ready.